2022
DOI: 10.3389/fmed.2022.853315
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Indocyanine Green Angiography and Swept-Source Wide-Field Optical Coherence Tomography Angiography in Posterior Uveitis

Abstract: PurposeTo compare indocyanine green angiography (ICGA) and swept-source wide-field optical coherence tomography angiography (SS-OCTA) for the assessment of patients with posterior uveitis.MethodSS-OCTA montage images of 5 x 12 x 12 mm or 2 x 15 x 9 mm, covering ~70–90 degree of the retina of consecutive patients with posterior uveitis were acquired. The choriocapillaries and choroidal slabs were compared to findings on ICGA.ResultsSixty-eight eyes of 41 patients were included (mean age 47.2 ± 20.4 years; 58.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…The limited field of view in commercially available instruments is a major disadvantage, as is the case for OCT, when compared to dye exams. The presentation of the retinal vasculature and choriocapillaris without the use of a dye was a revolution which led to theories that OCT-A could replace the dye exams which is absolutely not the case [24,25], but nevertheless stimulated the publication of articles attempting to oppose the two methodologies [26,27]. Indeed, OCT-A is of limited practical value in everyday routine clinical practice with limited valueadded information after other multimodal investigations have been performed [28].…”
Section: Optical Coherence Tomography Angiography (Oct-a)mentioning
confidence: 99%
“…The limited field of view in commercially available instruments is a major disadvantage, as is the case for OCT, when compared to dye exams. The presentation of the retinal vasculature and choriocapillaris without the use of a dye was a revolution which led to theories that OCT-A could replace the dye exams which is absolutely not the case [24,25], but nevertheless stimulated the publication of articles attempting to oppose the two methodologies [26,27]. Indeed, OCT-A is of limited practical value in everyday routine clinical practice with limited valueadded information after other multimodal investigations have been performed [28].…”
Section: Optical Coherence Tomography Angiography (Oct-a)mentioning
confidence: 99%
“…Images created by OCT-A montage are often used to compare with FA-ICGA, but the creation of this montage has many technical difficulties and, in the majority of cases, needs special software. As it is mentioned by Eastline et al, their study showed that 100% of montage-wide field OCTA images present artifacts, including but not limited to displacement-, shadowing- and artifact and vessel displacement [ 11 , 12 ]. Hypopyon, vitritis, and exudative detachment of the retina can also affect the quality of OCT-A…”
Section: Oct-a Technologymentioning
confidence: 99%
“…While OCT-A is very performing in analyzing retinal vessels in the posterior pole and can show choriocapillaris non-perfusion in some instances, it is ill-suited to analyze the choroidal stroma. It is, therefore, not surprising that there are so few publications on the use of OCT-A in the VKH [ 12 , 51 ]. Despite the inadequacy of the method for stromal choroiditis, rare reports tried to show the utility of OCT-A in the 6 × 6 posterior pole area analyzed by OCT-A [ 12 , 51 ].…”
Section: Use Of Oct-a In Clinical Practice For Specific Uveitis Condi...mentioning
confidence: 99%
See 2 more Smart Citations